Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1161/01.str.0000117238.75736.53
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Gene Haplotypes and Risk of Cerebral Small-Vessel Disease

Abstract: Background and Purpose-Genetic influences are important in multifactorial cerebral small-vessel disease (SVD) and may act via endothelial dysfunction. Nitric oxide (NO) synthesized by endothelial nitric oxide synthase (eNOS) is a key mediator of endothelial function. We determined the role of 3 potentially functional eNOS polymorphisms (T-786C, intron 4ab, G894T) located toward the 5Ј flanking end of the gene as risk factors for SVD and different SVD subtypes: isolated lacunar infarction (nϭ137) and ischemic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 37 publications
(36 reference statements)
11
114
3
4
Order By: Relevance
“…24 Intron 4A variant was also shown to be protective against cerebral small-vessel diseases with a confined effect to isolated lacunar infarction and suggested that the protective effect of the intron 4A could be mediated through changes in the eNOS promoter activity and increased NO levels. 15 Our results also showed the significant association of intron 4BB genotype with primary Table 4 Comparison of endothelial nitric oxide gene polymorphisms with diabetes and dyslipidemia hypertension and the protective effect of intron 4A allele against the disease. A significant excess of homozygotes for the rare intron 4A allele in patients with severely stenosed arteries in Australian subjects was reported, but the study did not provide an association with hypertension.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…24 Intron 4A variant was also shown to be protective against cerebral small-vessel diseases with a confined effect to isolated lacunar infarction and suggested that the protective effect of the intron 4A could be mediated through changes in the eNOS promoter activity and increased NO levels. 15 Our results also showed the significant association of intron 4BB genotype with primary Table 4 Comparison of endothelial nitric oxide gene polymorphisms with diabetes and dyslipidemia hypertension and the protective effect of intron 4A allele against the disease. A significant excess of homozygotes for the rare intron 4A allele in patients with severely stenosed arteries in Australian subjects was reported, but the study did not provide an association with hypertension.…”
Section: Discussionsupporting
confidence: 65%
“…28 Several other reports have suggested a combined protective effect of intron 4 and G894T or TÀ786C variants. 15,24,29 In our study, we observed a significant association of intron 4BB genotype with systolic blood pressure among subjects with BMI greater than 25 kg/m 2 . BMI is known to have an effect on blood pressure and atherosclerosis and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The present results indicate that polymorphisms in GCH1 (rs841) are independently associated with an increased risk for IS. In contrast, we failed to detect significant independent association with the rest of SNPs even though they have been suggested to be associated with cardiovascular diseases such as hypertension, coronary heart disease or stroke [21][22][23] .…”
Section: Discussioncontrasting
confidence: 90%